Applications of hypsometric relations and volumetry in seminal eucalyptus stand - Lafetá, Bruno Oliveira; Sampaio, João Marcos Barbosa; Milagres, Vitor Augusto Cordeiro; Fontan, Ivan da Costa Ilhéu; Vieira, Diego dos Santos; Santos, Erik Brian dos (Revista de Ciências Agroveterinárias, 2024)
Scientific investigations on the application of hypsometric relationships provide important support for quantification of wood resources and forest management. This research aimed to evaluate the effect of alternatives for the use of hypsometric relationships on height and volume in a seminal eucalypt stand. Forest inventory was carried out at 60 months of age and consisted random distribution of 10 sampling units. Two approaches were evaluated for the application of hypsometric relationships using different modeling methods, one which estimates height of all inventoried stems (P1, estimated heights) and other based on estimating the height of only those individuals who had only DBH measured (P2, combination of measured and estimated heights). Hypsometric relationships of the models fits of Curtis (linear regression), Logistic (non-linear regression) and support vector machines with radial basis Kernel function exhibited the best predictive qualities. Calculated volumes do not differ statistically between approaches P1 and P2. It is concluded that P1 approach is an alternative for application of properly established hypsometric relationships and does not compromise forest volumetric quantification. Biometric variability tends to be smaller with the estimation of the height of all inventoried stems.